ISLAMIC WORK ETHICS (IWE) - Hendryadi, Hendryadi (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
The purpose of this paper is to present a review of the empirical research of the Islamic work ethic (IWE) and its influence on business and management practices. This review summarizes the research on IWE from 2010 to 2017. Fifteen articles were selected during this period, resulting in two areas findings. First, the role of IWE on mainly HRM practices and work and individual related outcomes such as commitment, satisfaction, perceived justice, OCB, and turnover intention. In relation to the organizational context, IWE found to be positively related to innovation, and organizational performance. This paper can provide practitioners and academics with a better understanding of the concept of IWE, and its impact on individuals and organizations Keywords: Islamic work ethics, IWE